2022
DOI: 10.3390/en15145105
|View full text |Cite
|
Sign up to set email alerts
|

Technological, Economic, Social and Environmental Barriers to Adoption of Small-Scale Biogas Plants: Case of Indonesia

Abstract: By 2025, biogas is estimated to become a larger part of Indonesia’s energy mix. Biogas is a renewable energy source that also has economic and environmental advantages. Domestic biogas generation has been embraced in Indonesia as a response to the country’s energy security concerns in rural areas. Since the 1970s, 48,038 biogas plants have been built in the region. To fully develop this technology, Indonesia must discontinue relying on fossil fuels and substitute current fossil-fuel-based energy. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 59 publications
5
15
0
2
Order By: Relevance
“…Biogas technology has not yet developed in Indonesia because the agricultural and livestock waste produced cannot yet be utilized because the human resources of rural farmers are not yet able to process livestock waste into biogas due to technical, economic, and social factors [38]. Research [24] found that farmer education, distance from house to barn, disease, and number of livestock, as well as the price of LPG subsidized by the government are considered factors inhibiting the development of biogas technology.…”
Section: Constraints and Efforts To Develop Biogasmentioning
confidence: 99%
See 2 more Smart Citations
“…Biogas technology has not yet developed in Indonesia because the agricultural and livestock waste produced cannot yet be utilized because the human resources of rural farmers are not yet able to process livestock waste into biogas due to technical, economic, and social factors [38]. Research [24] found that farmer education, distance from house to barn, disease, and number of livestock, as well as the price of LPG subsidized by the government are considered factors inhibiting the development of biogas technology.…”
Section: Constraints and Efforts To Develop Biogasmentioning
confidence: 99%
“…A number of studies reveal that the perspectives of Indonesian society are diverse due to culture and traditions. As a result, biogas adoption varies greatly from one region to another, lacking government support to promote biogas technology [38]. Another study found that farmer literacy and education were still low in using biogas [42].…”
Section: Constraints and Efforts To Develop Biogasmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain itu, studi lebih lanjut harus dilakukan untuk lebih mengoptimalkan kinerja digester anaerob yang sesuai dengan karakteristik limbah yang dihasilkan secara lokal yang dimanfaatkan untuk produksi bio-metana (Amin et al 2022). Kebijakan yang diterapkan oleh negara-negara industri seperti Jerman dan Swedia harus dipelajari untuk mempercepat penyebaran teknologi biogas di daerah maupun perkotaan (Situmeang et al 2022). Dukungan dari pemerintah, organisasi koperasi dan industri semuanya harus didorong.…”
Section: Upaya Yang Dilakukanunclassified
“…Earlier studies present barriers to the functioning of agricultural biogas plants without any particular use of the typology (Pawlak, 2013;Mateescu et al, 2008). Other studies indicate the following barriers: political, economic, social, and technological (Situmeang et al, 2022;Igliński et al, 2020) supplemented with market barriers (Monjurul et al, 2022;Nevzorova & Kutcherov, 2019). At the same time, the literature points out the following issues applied to barriers to biogas technologies in rural areas: financial and economic; market; social and cultural; regulatory and institutional; technological and infrastructural, as well as information (Mittal et al, 2018).…”
Section: An Overview Of the Literaturementioning
confidence: 99%